Malta : Financial Sector Assessment Program-Technical Note-Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT). - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This technical note on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for the Malta summarizes the findings of a targeted review of several aspects of Malta's progress in addressing AML/CFT vulnerabilities in the financial sector, specifically the banking sector. The report recommends that while Malta has strengthened AML/CFT requirements for banks in recent years, the implementation of AML/CFT preventive measures should be improved further. Although important milestones have been implemented by the Financial Intelligence Analysis Unit and Malta Financial Services Authority to enhance AML/CFT supervision since mid-2017, recent AML/CFT violations raise doubts as to their capacity to effectively identify and address AML/CFT compliance breaches. A multiprong strategy is needed to address these deficiencies. The focus needs to be on developing more effective AML/CFT enforcement and ensuring that banks apply appropriate preventive measures in relation to their high-risk activities and clients. AML/CFT supervision needs to more stringently evaluate banks' risk mitigation models, ensure that customer due diligence requirements are properly followed, and apply corrective actions and sanctions when deficiencies are identified.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet